THE EFFECT OF STRATEGIC LEADERSHIP AND ROLE CONFLICT TO EMPLOYEE'S COMMITMENTS WITH WORK STRESS AS MEDIATION - Sajida, Priest Winka; Moeljadi, Moeljadi (Universitas Brawijaya, Indonesia, 2018)
The purpose of this research is to analyze the impact of strategic leadership and role conflict on employee commitment with job stress as mediation. The study used 60 samples of employees from BPR Nusamba Ngunut Tulungagung as respondents. Research data were obtained through questionnaires and analyzed through SmartPLS. The results show significance for the impact of strategic leadership to job stress, role conflict to job stress, role conflict to employee commitment, job stress to employee commitment, and insignificant results on the influence of strategic leadership to employee commitment. Job stress mediates the influence of strategic leadership and role conflict to employee commitment.